PTPN2, A Key Predictor of Prognosis for Pancreatic Adenocarcinoma, Significantly Regulates Cell Cycles, Apoptosis, and Metastasis - Kuang, Wenbin; Wang, Xiao; Ding, Jiayu; Li, Jiaxing; Ji, Minghui; Chen, Weijiao; Wang, Liping; Yang, Peng (Frontiers in Immunology, 2022)
Objective: This study conducted a comprehensive analysis of the members of the PTPN family and emphasized the key role of PTPN2 as a potential therapeutic target and diagnostic biomarker in improving the survival rate of PAAD. Method: Oncomine was used to analyze the pan-cancer expression of the PTPN gene family. The Cancer Genome Atlas (TCGA) data as well as Genotype-Tissue Expression (GTEx) data were downloaded to analyze the expression and prognosis of PTPNs. The diagnosis of PTPNs was evaluated by the experimental ROC curve. The protein-protein interaction (PPI) network was constructed by combining STRING and Cytoscape. The genes of 50 proteins most closely related to PTPN2 were screened and analyzed by GO and KEGG enrichment. The differentially expressed genes of PTPN2 were found by RNA sequencing, and GSEA enrichment analysis was carried out to find the downstream pathways and targets, which were verified by online tools and experiments. Finally, the relationship between PTPN2 and immune cell infiltration in pancreatic adenocarcinoma, and the relationship with immune score and immune checkpoint were studied. Result: The expression patterns and the prognostic value of multiple PTPNs in PAAD have been reported through bioinformatic analyzes. Among these members, PTPN2 is the most important prognostic signature that regulates the progression of PAAD by activating JAK-STAT signaling pathway. Comparison of two pancreatic adenocarcinoma cell lines with normal pancreatic epithelial cell lines revealed that PTPN2 expression was up-regulated as a key regulator of PAAD, which was associated with poor prognosis. Knockdown of PTPN2 caused a profound decrease in PAAD cell growth, migration, invasion, and induced PAAD cell cycle and apoptosis. In addition, we conducted a series of enrichment analyses to investigate the PTPN2-binding proteins and the PTPN2 expression-correlated genes. We suggest that STAT1 and EGFR are the key factors to regulate PTPN2, which are involved in the progression of pancreatic adenocarcinoma. Meanwhile, the silencing of PTPN2 induced the repression of STAT1 and EGFR expression. Conclusion: These findings provide a comprehensive analysis of the PTPN family members, and for PAAD, they also demonstrate that PTPN2 is a diagnostic biomarker and a therapeutic target.